(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2025)
Primary tuberculosis of the penis is extremely rare. A 2-year, 2-month-old uncircumcised toddler presented with a non-healing ulcer on the dorsum of the root and body of the penis. The diagnosis of tuberculosis was confirmed by histopathology and excellent response to antitubercular chemotherapy. There was no co-existing tuberculous infection elsewhere but there was a history of recent contact with a pulmonary TB patient. The chance of acquiring the disease through direct contact of penile skin with infected sputum. Children are not immune to penile tuberculosis. The possibility of tuberculosis as a cause of chronic ulcer on the penis has to be kept in mind especially in endemic countries. The importance of histopathological examination in the diagnosis of chronic genital ulcer is emphasized. Journal of Paediatric Surgeons of Bangladesh (2020) Vol. 11 (1 & 2):52-56